In-Hospital Mortality Among Patients with Acute Coronary Syndrome and Cardiogenic Shock Treated with Percutaneous Coronary Intervention and Intra-Aortic Balloon Pump - Zain Mehmood Butt, Naveed Iqbal, Mashooque Ali Dasti, Faraz Farooq Memon, Syed Tahir Hussain, Syed Nadeem Hassan Rizvi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The object of our research was to determine whether intra-aortic balloon pump-assisted PCI improved overall clinical outcomes during hospitalization, as well as to predict in-hospital mortality and cardiogenic shock. Methods: This retrospective study was carried out at National Institute of Cardiovascular Diseases Karachi. We enrolled 60 consecutive patients with a history of AMI complicated by cardiogenic shock. These patients underwent PCI with insertion of an IABP between 1st September 2019 and 28th February 2020. Patients with cardiogenic shock would have better survival if the IABP was inserted before PCI rather than after PCI was performed. The prospective study included 60 patients (33 patients received IABP before PCI, before and 27 after PCI) suffering from cardiogenic shock complicating acute myocardial infarction who underwent PCI with IABP. SPSS version 23.0 was used to analyze all the data. Results: Based on the type of treatment, we divided individuals into two groups in our study. The IABPs were inserted before PCI in 33 patients in group A, and the pumps were started after PCI in 27 participants in group B. It was significantly different regarding the 30-day mortality rate between IABP support after PCI and IABP-assisted PCI (59.2% versus 18.1%, respectively, p = 0.006). Among the entire study population, no reinfections or repeat PCI were reported. There was no significant difference between these two groups in the rates of emergency bypass surgery and cerebral vascular events. Practical Implication: This research study on in-hospital mortality among patients with acute coronary syndrome and cardiogenic shock treated with PCI and IABP has practical implications that benefit the community. It enhances patient outcomes, informs clinical decision-making, contributes to treatment guidelines and protocols, facilitates healthcare resource allocation, and inspires future research and innovation. Ultimately, the study aims to improve the quality of care provided to patients in this specific population, leading to reduced mortality rates and improved patient well-being Conclusion: This study concluded that PCI assisted by IABP results in a better outcome for patients with cardiogenic shock complicating acute myocardial infarction and a lower mortality rate compared to IABP after PCI. Keywords: In-hospital mortality, percutaneous coronary intervention, intra-aortic balloon pump.